Inhibition of SET domain–containing (lysine methyltransferase) 7 alleviates cognitive impairment through suppressing the activation of NOD-like receptor protein 3 inflammasome in isoflurane-induced aged mice. (9th February 2022) - Ma, Chao; Yu, Xianjun; Li, Dong; Fan, Youwen; Tao, Qiang; Tang, Yajun; Zheng, Lei
Background: As a common postoperative complication to elderly patients, postoperative cognitive dysfunction (POCD) is a central nervous system complication, often taking place after anesthesia and surgery. (Su(var)3-9, enhancer-of-zeste, and trithorax) domain–containing protein 7 (SETD7) plays important roles in metabolic-related diseases, viral infections, tumor formation, and some inflammatory reactions. However, the role and mechanism of SETD7 in POCD have not been previously studied. Methods: RT-PCR and Western blot were performed to evaluate the efficiency of knockdown of SETD7. The pathological changes of hippocampal neurons in isoflurane-anesthetized mice were detected by HE staining, and the Morris water maze experiment was performed to evaluate the learning and memory abilities of mice. The effect of SETD7 on the hippocampus in isoflurane-induced aged mice was examined by Western blot and TUNEL assay. Then ELISA assay was applied to determine the expression of some inflammatory cytokines, followed by the detection of expression of NOD-like receptor protein 3 (NLRP3) inflammasome through Western blot. Results: The data of this research revealed that SETD7 knockdown improved cognitive impairment in isoflurane-anesthetized mice, ameliorated cell pyroptosis, inhibited the release of inflammatory cytokines, and suppressed the activation of NLRP3 inflammasome in the hippocampus in isoflurane-induced aged mice. Conclusion: Collectively, these results provided evidence that the inhibition of SETD7 could alleviate neuroinflammation, pyroptosis, and cognitive impairment by suppressing the activation of the NLRP3 inflammasome in isoflurane-induced aged mice.